Is gold a hedge against stock price risk in U.S. or Indian markets? - Hemant Manuj (Risks, 2021)
We study whether gold acts as a hedge or a safe haven in U.S. and the Indian stock markets. These two stock markets have been chosen as representatives of the developed markets and the emerging markets, respectively, and are of significant interest to long-term investors. We apply a linear regression and a GARCH technique to monthly return series data on the S&P500, the BSE Sensex, and gold prices. We find that, for the period of our study, 1980-2020, gold has not served as a hedge or a safe haven for long-term investors in the U.S. or Indian stock markets. This holds true even across multiple sub-periods in our study period. Gold returns do not exhibit a significant negative relationship with stock returns in any of the chosen stock market scenarios, i.e., in times of extremely low returns as well as in the periods of high or low volatility. Equity investors in U.S. and Indian markets can use the findings of this study for optimising their portfolios. Additionally, central bankers and policy makers can use the findings for better outcomes with respect to their policies on holding of gold.
Keywords: 330; gold; hedge; India; portfolio; stocks